2020
DOI: 10.31557/apjcp.2020.21.8.2349
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Phytoconstituents, Antioxidant and Anti-Liver Cancer Activities of Saueda monoica Forssk Extracted by Microwave-Assisted Extraction

Abstract: Background: Wild edible plants are good sources for bioactive compounds, vitamins, and minerals with various applications. They can play a role in supporting the immune system and are highly beneficial as resources. Suaeda monoica Forssk is a wild edible plant that grows in Iraq and it's biological activities have not yet reported. Methods: Saueda monoica Forssk bioactive compounds were extracted by a microwave-assisted extraction method using ethanol as a solvent, and its chemical composition was analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Antioxidant activity According to Al-Shawi et al [26], used DPPH (2,2-Diphenyl1-picrylhydrazyl) method with some modification to examine the scavenger activity of new compounds. Different volumes (10-80) µl of synthesized compounds (4a-d) and vitamin C (1 mg/mL) were added to 200 µl of DPPH (1 mm) in 96 well/plate and left for 30 min in dark place.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Antioxidant activity According to Al-Shawi et al [26], used DPPH (2,2-Diphenyl1-picrylhydrazyl) method with some modification to examine the scavenger activity of new compounds. Different volumes (10-80) µl of synthesized compounds (4a-d) and vitamin C (1 mg/mL) were added to 200 µl of DPPH (1 mm) in 96 well/plate and left for 30 min in dark place.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…According to Al-Shawi et al [58], ow cytometry analysis identi ed the G1, S, and G2 phases for compounds 5 and 6b. a system with some modi cations.…”
Section: Cell Cyclementioning
confidence: 99%
“…Furthermore, the heterocyclic structures are the precursor to many anticancer agents on the market. Some studies [15][16][17] demonstrated the importance of 2-thioxo-4imidazolidinone in cancer treatment.…”
Section: Anticancer Activity Of 2-thioxo-4-imidazolidinone Derivativesmentioning
confidence: 99%